Evaluation of insecticide ear tags containing ethion for control of pyrethroid resistant Haematobia irritans (L.) on dairy cattle - Anziani, Oscar Sergio (2000)
A field study was conducted in central Argentina to evaluate the efficacy of ear tags containing 36% ethion against pyrethroid resistant populations of Haematobia irritans on grazing dairy cattle. The treated group consisted of 45 milking Holstein cows which received two tags per head and the control consisted of 22 dry cows from the same cohort. Treated and control groups were grazed on similar lucerne pastures separated for a minimum distance of 800m but they were not isolated from other cattle herds on the same or contiguous properties. In both groups, horn fly estimation were made weekly by examining cattle in the pastures with the aid of binoculars. The percentage reduction of fly numbers on treated cows was considered as efficacy of control provided by the tags. The ethion ear tags provided a range of 85-99% reduction in horn fly numbers for 16 weeks. During this period, the weekly mean number of H. irritans on the tagged cows ranged between 0.44 and 28.26 compared with 143.5 and 239.1 in control animals. The ethion ear tags could be a useful tool for the control of H. irritans mainly in areas where populations of this insect have developed resistance to pyrethroid insecticides. Copyright (C) 2000 Elsevier Science B.V.